Long-term Paleolithic diet is associated with lower resistant starch intake, different gut microbiota composition and increased serum TMAO concentrations - Genoni, A.; Christophersen, Claus; Lo, J.; Coghlan, Megan; Boyce, M.C.; Bird, A.R.; Lyons-Wall, P.; Devine, A. (2020)
© 2019, The Author(s). Background: The Paleolithic diet is promoted worldwide for improved gut health. However, there is little evidence available to support these claims, with existing literature examining anthropometric and cardiometabolic outcomes. Objective: To determine the association between dietary intake, markers of colonic health, microbiota, and serum trimethylamine-N-oxide (TMAO), a gut-derived metabolite associated with cardiovascular disease. Design: In a cross-sectional design, long-term (n = 44, > 1 year) self-reported followers of a Paleolithic diet (PD) and controls (n = 47) consuming a diet typical of national recommendations were recruited. Diets were assessed via 3-day weighed diet records; 48-h stool for short chain fatty acids using GC/MS, microbial composition via 16S rRNA sequencing of the V4 region using Illumina MiSeq. TMAO was quantified using LC–MS/MS. Results: Participants were grouped according to PD adherence; namely excluding grains and dairy products. Strict Paleolithic (SP) (n = 22) and Pseudo-Paleolithic (PP) (n = 22) groups were formed. General linear modelling with age, gender, energy intake and body fat percentage as covariates assessed differences between groups. Intake of resistant starch was lower in both Paleolithic groups, compared to controls [2.62, 1.26 vs 4.48 g/day (P < 0.05)]; PERMANOVA analysis showed differences in microbiota composition (P < 0.05), with higher abundance of TMA-producer Hungatella in both Paleolithic groups (P < 0.001). TMAO was higher in SP compared to PP and control (P < 0.01), and inversely associated with whole grain intake (r = − 0.34, P < 0.01). Conclusions: Although the PD is promoted for improved gut health, results indicate long-term adherence is associated with different gut microbiota and increased TMAO. A variety of fiber components, including whole grain sources may be required to maintain gut and cardiovascular health. Clinical trial registrations: Australian and New Zealand Clinical Trial Registry (ANZCTRN12616001703493).